Prevalence and impact of bullying in a portuguese school: insights from a descriptive cross-sectional study - Catarina M. Francisco; Íris Santos Silva; Alexandra M. Rodrigues; Lara Torres; Pedro Fernandes; Rita S. Oliveira (Portuguese Journal of Pediatrics)
Introduction and Objectives: Bullying is defined as peer violence, characterized by repeated aggression over time, the intention to cause suffering to others and an imbalance of power between the two sides. The authors set out to quantify the prevalence of bullying and characterize students’ engagement and perception of bullying incidents. Methods: Descriptive cross-sectional study, in the form of a survey for students at a local school. A total of 199 children were surveyed, of which 55% were male and the median age was 11. Results: In terms of suffering from bullying, 60.3% (n = 120) answered affirmatively, with 41% (n = 81) having endured an episode in the past six months. About 8% mentioned attacks the previous week. Discussion: Most of the bullying episodes happened among children from the same class (23.6%), and the most common place of occurrence was the playground. Around 46.5% perceived school as a dangerous place. Regarding gender, bullying was more frequent in males (p = 0.013).